Annual Housing Survey, 1981 (United States): National File ([Verlag nicht ermittelbar], 1984)
This data collection provides information on the characteristics of a national sample of housing units. Data include the year the structure was built, type and number of living quarters, presence of a garage, occupancy status, access, number of rooms and bedrooms, presence of commercial establishments on the property, and property value. Additional data focus on kitchen and plumbing facilities, types of heating fuel used, source of water, sewage disposal, heating and air conditioning equipment, and major additions, alterations, or repairs to the property. Information provided on housing expenses includes monthly mortgage or rent payments, cost of services such as utilities, garbage collection, and property insurance, and amount of real estate taxes paid in the previous year. Similar data are provided for housing units previously occupied by respondents who had recently moved. Supplemental sections provide data on energy-related characteristics, such as the presence of storm doors, storm windows, and other types of insulation, and use of supplemental heating equipment. Additionally, indicators of housing and neighborhood quality are supplied. Housing quality variables include privacy of bedrooms, condition of kitchen facilities, basement or roof leakage, cracks or holes in walls, ceilings, and floors, breakdowns of plumbing facilities and equipment, use of exterminator service, and respondent's overall opinion of structure. For quality of neighborhood, variables include existence of boarded-up buildings, noise, lack of street lighting, heavy traffic, objectionable odors, crime, and respondent's overall opinion of neighborhood. In addition to housing characteristics, demographic data are provided on the household members, such as sex, age, race, marital status, relationship to the household head, and income. Additional data are supplied on the head of the household including years of school completed, Hispanic origin, and length of residence. For all employed respondents, travel-to-work information such as principal mode of transportation, carpool occupancy, type of public transportation used, and time and distance from home to work was also collected.